2005
DOI: 10.1002/eqe.519
|View full text |Cite
|
Sign up to set email alerts
|

Operator‐splitting method for real‐time substructure testing

Abstract: SUMMARYIt has been shown that the operator-splitting method (OSM) provides explicit and unconditionally stable solutions for quasi-static pseudo-dynamic substructure testing. However, the OSM provides only an explicit target displacement but not an explicit target velocity, so that it is essentially an implicit method for real-time substructure testing (RST) when the velocity-dependent restoring force is considered. This paper proposes a target velocity formulation based on the forward di erence of the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 17 publications
0
71
0
Order By: Relevance
“…Therefore, Wu et al, [75] proposed an unconditionally stable predictorcorrector method based on the OSM that is explicit when applied in a RTHT.…”
Section: Operator-splitting Techniquesmentioning
confidence: 99%
“…Therefore, Wu et al, [75] proposed an unconditionally stable predictorcorrector method based on the OSM that is explicit when applied in a RTHT.…”
Section: Operator-splitting Techniquesmentioning
confidence: 99%
“…Wallace et al [15] determined that when the time delay in the restoring force in the system exceeds a critical value, that system becomes unstable. Wu et al [16] investigated the stability of an SDOF system in presence of actuator delay during a real-time test. Horiuchi et al [8] studied the effects of actuator delay in a real-time test, by means of energy balance approach and showed that a delay by an actuator causes increase in energy content of the system.…”
Section: Introductionmentioning
confidence: 99%
“…It solves the equations of motion in a computer by using the restoring forces obtained from an associated quasi-static test. When the substructuring technique is adopted, the online hybrid test, commonly referred to as the substructural online hybrid test [5][6][7][8][9][10][11][12][13], is capable of handling large-scale structures. The substructures can be distributed to geographically different locations connected via Internet [11][12][13], which greatly expands the capacity of the online hybrid test.…”
Section: Introductionmentioning
confidence: 99%